A rare case of multiple congenital malformations in a piglet - Menegatos, J.; Stoforos, E.; Deligiorgis, S.; Xylouri, E. (Journal of the Hellenic Veterinary Medical Society, 2019)
It is described a case of multiple congenital malformations in a Landrace male piglet which lived for 50 days. It showed brachygnathia superior, arthrogryposis of hind limbs, malformations of the lumbar vertebrae and the sacrum, aplasia of the left ilium and of the muscles of the lift thigh and femur. Also all the bones of the left hind limb were shorter than the right ones. Malformations of the sternum and the ribs were present. The left ribs were shorter than the right ones The left lung, kidney and testicle were much shorter than the right ones. The causative agent was unknowh.